Generating usable electric power while sensing glucose. (1st November 2017) - Kulkarni, Tanmany; Slaughter, Gymama
Abstract : Herein a system capable of simultaneously sensing glucose and harnessing sufficient energy to power a digital device is presented. This system is powered by an enzymatic glucose biofuel cell consisting of pyroloquinoline quinone glucose dehydrogenase‐modified bioanode and bilirubin oxidase‐modified biocathode. The electrical parameters from a single biofuel cell were amplified to 1.4 V using a charge pump circuit consisting of a capacitive element that senses glucose. Furthermore, a steady output DC supply of 3.2 V was obtained by interfacing a step‐up DC convertor circuit to the charge pump circuit. Such a system simultaneously senses glucose and harnesses energy in the presence of various glucose concentrations. The self‐powered glucose biosensor exhibited an improved sensitivity of 86.42 Hz/cm 2 mM with a linear range extending to 20 mM when operating a digital device simultaneously. This is a 3.7‐fold increase in sensor sensitivity when compared with previous self‐powered glucose biosensors. This novel self‐powered glucose biosensing system shows a promising future for powering implantable devices and assessing patient health.